Rapid Production Ramp-up for International Collaborative Supply Network in Electronics Goods Industry (X-Box, PS II, I-Pod, Etc) A Review of Existing Practices, Issues, and Challenges - Hu, Ning (2006)
The fierce competition of international consumer electronics market has brought more pressures on the manufacturing section especially in the context of globalization. The global producers have to find effective solution to cope with the challenges such as shorter and shorter product life, less and less customer loyalty and resources limitation. The fact that rapid production ramp up and supply network collaboration could benefit their performance has been recognized by many business giants such as Microsoft, Sony and Apple. Their products, X-box, PS II and iPod have gotten outstanding performances in the market due to the right strategies and detailed operations. This paper reviews their practices and examines the issues and challenges which they had to deal with. It also develops a framework which illustrates the relative issues of implementing the process of rapid production ramp up for collaborative supply networks in the consumer electronics goods industry. This framework could help the manufacturing managers to get better understanding of this process and optimize their operations.